4 - Le Management africain: Mythe ou Réalité? by Amadou Lamine DIA - Amadou Lamine DIA, (Africa Development, 1990)
African management today, etaentially characterized by a traditional style of man agement - whereby managers act on behalf of and for the group from which they originated - as well as a personal style of management - whereby authority and decision-making are concen trated in the hands of the omnipresent company head - is the main reason for the failure in Africa of companies which too often are unviable, neat competitive and short-lived. This type of management should therefore become a myth and be rapidly replaced by a new and real Afri can management, which would not deny African cultural specificities but would associate them with principles of strictness, rationality and method. These principles characterize western man agement, but their value and efficiency must be regarded as universal.